Brand Extensions in a Competitive Context: Effects of Competitive Targets and Product Attribute Typicality on Perceived Quality - Han, Jin K. (Institutional Knowledge at Singapore Management University, 1998)
Brand extensions have proliferated over the past decade, and the rationale behind endowing a new product with a well-known brand name is to provide consumers--and the trade--with a sense of familiarity and security by leveraging positive brand characteristics in a new product category. Although brand extensions have become a standard strategy for new product introductions in today's fiercely competitive marketplace, the extant literature has examined brand extensions as if they occur in a competitive vacuum. This study attempts to fill this void by examining brand extensions in a competitive context. Specifically, brand-extension strategy in a competitive context includes two key decisions: (1) whether the brand should be compared against the prototypical brand of the extension category, against a nonprototypical brand, or whether a comparison should be avoided; and (2) whether typical attributes of the extension category or atypical ones should be highlighted. In two experiments, we use comparative and noncomparative ads as vehicles in exploring the two key decisions of brand extension strategy in a competitive context. Our findings suggest that, if there is a high fit between the established image of a brand and the extension category, a brand extension with attributes that are perceived to be typical in the extension category is judged to be of higher quality when consumers evaluate the brand extension on its own grounds rather than in comparison with brands in the extension category. In contrast, when the brand does not fit easily with the extension category, the brand with typical attributes is judged to be of higher quality if the brand is positioned explicitly against the prototypical brand of the extension category. Finally, in cases in which the brand's attributes in the extension category are atypical (i.e., the brand possesses attributes that differentiate it from other brands in the extension category), positioning the brand against the category prototype is generally preferable to the noncomparative format. Overall, low-fit brand extensions were generally judged to be of lower quality than high-fit brand extensions, and neither the ad format nor the type of attribute could overcome the negative effects of low fit.